Lifting platform and vehicle - LUO CHENGYAO; XIE JIAWEN; LIU XUEMEI; ZHU LIANGYI (2025)
The utility model discloses a lifting platform and a vehicle, the lifting platform comprises a bearing device and a first lifting adjusting device, the bearing device is suitable for placing a bearing object; one end of the first lifting adjusting device and the bearing device are provided with at least two connecting points, the other end of the first lifting adjusting device is suitable for fixing the bearing device, and the maximum distance difference value between the at least two connecting points and a reference plane is smaller than a preset distance value. The lifting platform can achieve stable and safe take-off and landing of the unmanned aerial vehicle under the bumpy road condition according to the fact that the maximum distance difference value between the at least two connecting points and the reference plane is smaller than the preset distance value. 本实用新型公开了一种升降平台及车辆，升降平台包括承载装置和第一升降调节装置，所述承载装置适于放置承载物；所述第一升降调节装置的一端与所述承载装置至少具有两个连接点，所述第一升降调节装置的另一端适于固定所述承载装置，至少两个所述连接点与参考平面之间的最大距离差值小于预设距离值。所述升降平台可根